Pengaruh Dana Alokasi Umum (DAU) dan Pendapatan Asli Daerah (PAD) terhadap Belanja Daerah Kota Bukittinggi Tahun 2006 - 2020 - Nasfi, Nasfi; Asnah, Asnah; Febrianti, Eka; Sabri, Sabri (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2021)
This research was conducted in the City of Bukittinggi, with the aim of research to determine the effect of general allocation funds on regional expenditures and to determine the effect of regional original income on regional expenditures as well as to determine and analyze the effect of general allocation funds and regional original revenues together on regional expenditures in Bukittinggi City period. 2016-2020. The research method is descriptive and quantitative data analysis with multiple linear analysis, with the help of SPSS 16 software testing. The research findings and the results of the general fund allocation variable have a significant effect on regional spending in Bukittinggi City, with the results of the statistical t test Tcount > Ttable with a significant value of 0.040 < 0, 05, the local original income variable has a significant positive effect on regional expenditure with the result that the value Tcount > Ttable is significant 0.019 and the variable general allocation fund and regional original income simultaneously has a positive and significant effect on regional expenditure in Bukittinggi City in 2016 to 2020 at the value of Tcount > Ttable with a significant value of 0.000 <0.05.